New Arm-Stretching-Type Anti-Slide Pile Design and Verification - Chen, Guangfu; Zhang, Guodong; Guo, Fei; Wang, Li; Zhan, Qinghua; Huang, Xiaohu (Frontiers in Earth Science, 2022)
Anti-slide piles play an important role in landslide control. However, owing to a limitation in the slide–resist design concept, large landslides are difficult to control. Moreover, the displacements of controlled projects are significant. In this paper, we propose an improved anti-slide pile design concept that develops and utilizes the landslide body. On this basis, we also design an arm-stretching-type anti-slide pile structure. We establish formulas for calculating the internal forces of this structure. The results of a case study indicate that the maximum shear force and bending moment of the arm-stretching-type anti-slide pile body were reduced by 43.6% and 25.4%, respectively, compared with those of a conventional single pile. Furthermore, the results of numerical modeling indicate that the arm-stretching-type anti-slide pile could significantly reduce landslide displacement. Thus, the proposed design is expected to solve the problems encountered when using conventional anti-slide piles for landslide control and can thereby become widely applicable in practice.